RESEARCH PHYSICAL AND MECHANICAL PROPERTIES AND DURABILITY OF SULFUR CONCRETE - Amanova, Nodira; Turaev , Khayit; Alikulov , Rustam; Khaitov , Bozar; Eshdavlatov , Erkin; Makhmudova , Yulduz (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: The article presents the physical and mechanical properties of sulfur concrete based on the modifier sulfur-PEM (maleic anhydride and polyhydric alcohol). The research resulted in the development of a new type of concrete. This innovative concrete was produced using sulfur-PEM modification and aggregate components. The resistance of concrete to freezing, durability, and elastic modulus of the studied sulfur-containing concrete were studied.